Revisiting the foreign language effect on moral decision-making: a closer look at the role of perverse responses - Feng, Chun; Liu, Chuanjun; Nolasco, Edgar Emmanuel (Journal of multilingual and multicultural development, 2025)
The present study examined the potential bias of foreign language effect (FLE) on moral judgment by considering the confounding influence of perverse responses. A perverse response is a reaction that contradicts both norms and consequences, that is, participants choose to take action (or inaction) when both norms and consequences require inaction (or action). We predicted that using a foreign language, compared to a native language, would elicit more perverse responses, thereby confounding the participants' moral judgments. To test our prediction, we distinguished between active and inhibitory perverse responses and re-analyzed the raw data from a previous FLE study using four approaches: the traditional dilemma paradigm, the process dissociation model, the consequence-norm-generalised inaction/action (CNI) model, and the consequence-overall action/inaction-norm (CAN) algorithm. The results of the mediation analyses consistently showed that active and inhibitory perverse responses mediate the effects of foreign/native language on moral decisions in all the four approaches. The results suggest that individuals using a foreign language tend to exhibit more active and inhibitory perverse responses, which in turn influence their moral decisions. Addressing this issue could help clarify the FLE on moral decision-making.